APPRAISING TWITTER USERS’ ATTITUDE ON “WRITING LAST LINE STORY”: SFL APPROACH ON CLOSING STATEMENT IN CYBER LITERATURE - Afriliani, Afriliani (Premise: Journal of English Education and Applied Linguistics, 2022)
Twitter, an online platform that is said to have a more constructive and meaningful response to the issues, is also where people are creative writers of cyber literature. Lately, there has been a trend of Twitter users to write fiction lines that have a premise of “what is your last line if you in the ending of a relationship.” This research intended to seek the attitude of Indonesian writing fiction in English. This paper analyses a short written online discourse called ‘tweet’ using Systemic Functional Linguistics (SFL). This analysis focuses on appraising attitudes that are feeling on reacting to emotion, putting the judgment, and evaluating things. The data is taken from a Twitter account, namely @literarybase, by shorting 100 popular tweets taken to seek the trend and 20 tweets among them to be classified on its appraisal criterion. The results show that a relationship's trend ends with a sad ending rather than a happy ending. However, positive affection holds the most significant shares of lexical choice, followed by judgment and appreciation the least. That means the users mostly used ironic writing that contrasts expectation with reality. Linguistic research also implied that tragedy plot is favorable in online discourse. The study has identified the practical way of assessing attitudes in short-writing fiction on online platforms and the tendency of a community to see value in a relationship and how they express themselves in a foreign language.